Pendidikan Kewarganegaraan Sebagai Penguatan Pendidikan Karakter Anak Usia SD Di Era Society 5.0 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
A country relies heavily on its civic education. Education makes countries progress and develop. Technological advances can have a positive or negative impact on education. There are benefits to using technology today, such as the pandemic, because lessons are conducted online. However, the negative effect is that it makes the younger generation addicted to technology. Even the era of society 5.0 can influence children's character. By instilling Pancasila values from an early age, it is hoped that the younger generation will become more aware of the importance of Pancasila for Indonesia. This article was written to determine to what extent and how the younger generation applies the principles of Citizenship Education. Analysis uses a descriptive approach and data is collected from book and journal sources. The research results show that in the last two years, especially in the millennial generation, there has been a lack of implementation of the values of Citizenship Education as strengthening children's character.